(untitled) (Journal of Scientific Research, 2009)
Biologically important polyphenol (+)-catechin was isolated from catechu, the extract of the red heartwood of Acacia Catechu tree (Khoiyer tree). The isolation procedure was developed to get better yield (25%) and to reduce the isolation cost and time. The structure of the isolated (+)-catechin was confirmed with several spectral analyses and chemical studies. Keywords:Â Acacia Catechu; (+)-catechin; Polyphenol. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. Â DOI: 10.3329/jsr.v1i2.1635